MODERNISING SITE-BLOCKING MECHANISM IN PROTECTING COPYRIGHT OWNERS CONTENT AGAINST DIGITAL PIRACY IN MALAYSIA - Mohd Syaufiq Abdul Latif; Nazura Abdul Manap; Nabeel Mahdi Althabhawi (Malaysian Journal of Syariah and Law)
The rapid evolution of digital technology and the widespread demand for online content have facilitated the rise of digital piracy, posing significant challenges to copyright protection. In Malaysia, digital piracy undermines copyright owners' revenue potential and creative incentives, causing substantial financial losses across various industries. Malaysia has incorporated site-blocking mechanisms under section 263 of the Communications and Multimedia Act 1998 and section 43C(2) of the Copyright Act 1987 to combat this issue. These measures aim to disrupt access to websites hosting pirated content, deterring illegal copyright consumption. However, the effectiveness of these mechanisms is continually challenged by the adaptive tactics of digital pirates, jurisdictional limitations, and technical workarounds that allow access to pirated content despite blocking attempts. Determining whether these site-blocking mechanisms effectively protect copyright owners' content against digital piracy necessitates a thorough evaluation of their strengths and weaknesses and a consideration of modern strategies for improvement within those acts. This paper hence will explore the current overview of site-blocking in Malaysia, identify the gaps in improvements and propose recommendations for enhancing the site-blocking frameworks to more effectively combat digital piracy and protect copyright owners' content against digital piracy in the currently evolving digital space.